Perspective directions optimization of process of long-term preparation of young sportsmen (on the example of team games) - Maksimenko I.G (Kharkov National Pedagogical University, 2012)
The purpose of work consisted of formulation of perspective directions optimization of the system of long-term preparation of young sportsmen, traditionally folded in Ukraine. In the article on the basis of analysis of materials foreign and domestic literary and Internet-sources, and also analysis of practical experience of leading specialists an attempt to generalize theoretical-and-methodical positions of the system of long-term preparation of reserve in team games is undertaken. The state of problem, related to optimization of process of preparation of young sportsmen is considered, and the possible ways of decision of the folded problem are offered.